2021
DOI: 10.1093/sleep/zsab272
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea is an independent risk factor for severe COVID-19: a population-based study

Abstract: Study Objectives Obstructive sleep apnea (OSA) has been proposed as a risk factor for severe COVID-19. Confounding is an important consideration as OSA is associated with several known risk factors for severe COVID-19. Our aim was to assess the association of OSA with hospitalization due to COVID-19 using a population-based cohort with detailed information on OSA and comorbidities. Methods Included were all community-dwelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…The principal finding in our study was that OSA is associated with COVID-19 infection and hospitalization after adjustment for multiple medical comorbidities including BMI. Our results are consistent with many other studies demonstrating that OSA appears to be a risk factor for COVID-19 infection or hospitalization [5][6][7][8]10,12,[14][15][16][17]31,32 as for influenza. 33 However, these prior studies utilized hospital records or other databases to identify COVID-19 cases with or without OSA and in some cases were susceptible to collider bias.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The principal finding in our study was that OSA is associated with COVID-19 infection and hospitalization after adjustment for multiple medical comorbidities including BMI. Our results are consistent with many other studies demonstrating that OSA appears to be a risk factor for COVID-19 infection or hospitalization [5][6][7][8]10,12,[14][15][16][17]31,32 as for influenza. 33 However, these prior studies utilized hospital records or other databases to identify COVID-19 cases with or without OSA and in some cases were susceptible to collider bias.…”
Section: Discussionsupporting
confidence: 93%
“…2,3 For example, among approximately 10,000 COVID-19 decedents during mid-February through mid-May 2020, nearly three-quarters had one or more underlying medical conditions (76.4%) or were aged ≥65 years (74.8%). 4 While these risk factors garnered considerable attention, in many, [5][6][7][8][9][10][11][12][13][14][15][16][17] but not all studies, [18][19][20] obstructive sleep apnea (OSA) was identified as a risk factor as well. The degree to which OSA represents an independent risk factor for adverse COVID-19 outcomes is uncertain; in several investigations, the impact of OSA was observed to be partially or completely explained by the presence of obesity and/or other comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…The overlap of risk factors for severe COVID-19 and OSA, namely Initially, data on the influence of OSA on COVID-19 outcomes were contradictory when confounders like obesity were added in the analysis models [8]. However, recent large studies and meta-analyses suggest that OSA is a mild-to-moderate risk factor for adverse outcomes in COVID-19, including increased rates of hospitalisation and need for intensive care, as well as mortality [3,[11][12][13]. One of the most comprehensive analyses, to date, on factors predicting adverse COVID-19 outcomes was published by BELLOU et al [3].…”
Section: The Relationship Between Sars-cov-2 Infections and Sleep Dis...mentioning
confidence: 99%
“…Two recent papers have addressed this question. A large Icelandic cohort of PCR-verified COVID-19 patients (n=4756) was linked with the clinical cohort of known OSA patients to identify OSA patients with COVID-19 (n=185) [12]. Severe COVID-19, defined as hospitalisation and/or death, was fivefold more common in OSA patients compared with the remaining Icelandic inhabitants (odds ratio 5.6), but after adjustment for confounders like age, sex, body mass index and comorbidities, the odds ratio was reduced to 2.0 (95% CI 1.1-3.6).…”
Section: The Use Of Pap Treatment During the Covid-19 Pandemicmentioning
confidence: 99%
“…In addition, obesity constitutes an important common risk factor for both conditions. It is probably on this basis that patients with OSA were found with higher rates of hospitalization, intensive care admission, and mortality ( 26 29 ). Moreover, patients with OSA overexpress the angiotensin-converting enzyme 2 (ACE2) receptor in response to hypoxemia, which can explain the higher infection rate observed in this population ( 28 , 30 ).…”
Section: Introductionmentioning
confidence: 99%